Climate Change for Sustainable Development: The Imperative of Indigenous Language Approach as a Remedy - Erhun, Mercy O. (African Journal of Stability and Development (AJSD), 2019)
Human activities have continued to increase the atmospheric concentration of greenhouse gases resulting in additional warming of the earth’s surface and the general atmosphere. One of the major threats to the global order in the present century is climate change. Climate change is one of the most important menaces to earth’s biodiversity, natural resources, poverty eradication etc., posing a threat to livelihoods and poverty reduction. The abounding evidence of global climate change can no longer be ignored. There is therefore the need to reinforce the management of risk as well as proactive actions in addressing climate change issues. Considering the negative impact of the menace of climate change on development, the ecosystem and mankind, this work appraises those measures put in place to checkmate the rising tide of greenhouse gas emission. To this end, this paper will study Nigeria’s environmental legal framework which will enable Nigeria’s ecosystem to naturally adapt to climate change that will lead to sustainable economic development. This paper found that Nigeria is ill-prepared to combat the challenges of climate change. Existing legal and institutional frameworks for the regulation of climate change in Nigeria are in fragmented forms while laws and implementation strategies for environmental protection concerning climate change in Nigeria are incoherent. This paper also found that there are no effective infrastructures to monitor and enforce climate change issues and that indigenous people are not well acquainted with the threats posed by climate change as a result of lack of effective communication posed by language barrier. This poses a challenge to the slogan of “acting for the long-term in a short-term world.” This paper concludes that there is an urgent need for a comprehensive framework that will create adequate awareness of the challenges of climate change, inclusively, to ensure proper understanding of citizens, so as to effectively regulate climate change in Nigeria. Hence, the indigenous language approach of this paper.